The effect of sensing ability In perceived value to customer: applied research in Iraqi private colleges (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Purpose: this paper, The main research idea is to identify the effect of sensing ability on the customer’s perceived value in private colleges in Baghdad. The research problem was: Has the sensing ability been used in the customer’s perceived value? efficiency in investing in customer attraction, To meet the needs of its customers and clients in the external environment with the required effectiveness, that is, it tries to achieve a balance between the elements of the internal and external environment, and this guarantees the organization’s agility. Descriptive analysis  It was distributed to a sample consisting of (242) individuals from the members of the private college councils and their teaching staff, which number (4) private college(al-mansour, al-rafidain, djlaa and albayan), using resolution and curriculum and curriculum analysis. from the research community represented by the Iraqi private colleges in Baghdad and recognized by the Ministry of Higher Education and Scientific Research for the year 2022/2023, and after processing Data using the statistical tools available within the statistical program (SPSS.V28) (percentage of agreement, arithmetic mean, standard deviation, coefficient of variation, Pearson correlation coefficient, simple linear regression, multiple linear regression, and path analysis), The Results confirmed the validity of the research hypotheses from which the research began, at both the general and individual levels. The researcher came to a number of conclusions, the most important of which is the presence of the research variables to statistically acceptable degrees within the researched organizations, as well as the strength of the mutual relationships and influence on them. We propose a future research agenda and highlight proactive customer engagement and organizational agility .The research results yielded (simple linear regression and regression Multilinearity and path analysis  There is an acceptable degree of effect between the research variables